Poor insight and future thinking in early dementia limit patient projections of potential utility of technological innovations and advanced care planning - McLaren, Jaye E.; Shin, Marlena H.; Moo, Lauren R. (Frontiers in Medicine, 2023)
Introduction: Cognitive psychology posits that thinking about the future relies on memory such that those with memory impairment may have trouble imaging their future technology and other needs. Methods: We conducted a content analysis of qualitative data from interviews with six patients with MCI or early dementia regarding potential adaptations to a mobile telepresence robot. Using a matrix analysis approach, we explored perceptions of 1) what technology could help with day-to-day functioning in the present and future and 2) what technology may help people with memory problems or dementia stay home alone safely. Results: Very few participants could identify any technology to assist themselves or other people with memory problems and could not provide suggestions on what technology may help them stay home alone safely. Most perceived that they would never need robotic assistance. Discussion: These findings suggest individuals with MCI or early dementia have limited perspectives on their own functional abilities now and in the future. Consideration of the individuals’ diminished understanding of their own future illness trajectory is crucial when engaging in research or considering novel technological management solutions and may have implications for other aspects of advanced care planning.